Шотландская сказка: Роман / Э. Вулф; пер. с англ. - Вулф Энн (Панорама романов о любви, 2006)
Экземпляры: (20190125) / Инвентарный номер: 36290 / Цена: 20.00 / Сис.шифр: И / Авт.знак: В88 / ГРНТИ: 17 / ББК: 84